An analytical approach to evaluate service coverage in slow frequency-hopping mobile radio systems. - Chiani, M.
The performance of a time-division multiple-access mobile radio system adopting slow frequency hopping is analyzed by following an original procedure that allows the evaluation of thermal noise and fast fading (e.g., Rayleigh) effects on block-coded transmission with nonideal interleaving. Starting from this approach, service coverage can be analytically evaluated when the ?slow? disturbances affecting the transmission are fixed. The method proposed is able to take several impairments and parameters into account, such as shadowing and discontinuous transmission. The experimental results confirmed the validity of the theoretical approach
Keywords: Block-coded transmission; Discontinuous transmission; Fast fading; Nonideal interleaving; Service coverage; Shadowing; Slow frequency-hopping mobile radio systems; Thermal noise; Time-division multiple-access mobile radio system